اتجاهات الأولياء نحو تأطير أبنائهم خلال فترة الحجر الصحي - زيكيو, مصطفى; خالد خوجة, صديق (جامعة الوادي - University of Eloued, 2021)
نحاول من خلال هذه الورقة البحثية التركيز على انعكاسات انتشار وباء كوفيد 19 على العملية التعليمة ،باعتبارها من الأنساق الأكثر تضررا من جراء تفشي هذا الوباء،وقد أدت الإجراءات الوقائية للحد من انتشار هذه الجائحة إلى حدوث إضطراب في العملية التعليمية في جميع دول العالم ومن بينها الجزائر،ونركز في هذا المقال على أراء أولياء التلاميذ بخصوص الشلل الذي أصاب المؤسسات التربوية من جراء الإغلاق العام ،وكذلك المخاوف التي تنتابهم حيال المستقبل الدراسي.وقد استخدمنا في هذه الدراسة أداة المقابلة باستعمال البريد الإلكتروني،حيث قمنا باختيار المبحوث الأول من أولياء التلاميذ بطريقة قصدية،ثم بدأ حجم العينة يزداد عن طريق ما يسمى في لغة الإحصاء بالكرة الثلجية.وقد بينت الدراسة أن هناك مخاوف حقيقية لدي أولياء التلاميذ بخصوص المستقبل الدراسي لأبنائهم ،وخاصة صعوبة اندماج الابناء في العملية التعليمية بالإضافة إلى الخوف من نسيان الأبناء كل ما درسوه خلال السنوات الماضية. Abstract: Through this research paper, we try to focus on the implications of the spread of the Covid 19 pandemic on the educational process, as it is one of the fields most affected by the outbreak of this epidemic, and the preventive measures have led to a disturbance in the educational process in all countries of the world, including Algeria.In this article, we focused on the opinions of students parents regarding the paralysis that afflicted the educational process as a result of the total closure, as well as the fears they have about the academic future. We have used in this study the interview tool using e-mail, where we chose the first respondent from students and their parents in an intentional way, then the sample size began to increase through what is called in the language of statistics with snowball. The study showed that there are real concerns among the pupils' parents regarding the educational future of their children, especially the difficulty of integrating children into the educational process due to the long interruption of their studies, in addition to the fear of forgetting everything they studied during the past years.
Parents’ attitudes towards framing their children during the quarantine period
مقال
Keywords: إضطراب العملية التعليمية، التلاميذ، انشغالات أولياء التلاميذ، المطالعة، الحجر الصحي; Disruption of the educational process, Students, the preoccupations of the students' parents, reading, Quarantine.